Effects of vacancies on structural, electronic, mechanical, and thermodynamic properties of C40-VSi2. Issue 15 (3rd August 2022) - Feng, Zhiqi; Duan, Yonghua; Shen, Li; Peng, Mingjun; Qi, Huarong
ABSTRACT: In our work, to figure out the effects of V and Si vacancies on formation energies, elastic properties, phonon dispersions, electronic structures, and thermodynamic properties of VSi2, we used first-principles calculations. VSi2 with V and Si vacancies are dynamically and thermodynamically stable from the calculated formation energies and phonon dispersions. Moreover, VSi2 with V and Si vacancies are mechanically stable certified by single-crystal elastic constants. The presence of different atomic vacancies can weaken the bond strength of V–Si and Si–Si bonds, and eventually leads to the decreasing phase stability and elastic modulus, but can increase elastic anisotropy and ductileness. Finally, thermodynamic properties, including Debye temperature, sound velocities, and directional sound velocities, of perfect VSi2 and VSi2 with different vacancies are calculated. Highlights Based on the calculated vacancy formation energies and phonon dispersions, the perfect VSi2 and VSi2 with different vacancies are thermodynamically and dynamically stable. The vacancies can reduce the thermodynamical stability of VSi2, VSi2 with V vacancies are more stable than those with Si vacancies, and among VSi2 with vacancies, VSi2 with V-Va1 is the most stable. The perfect VSi2 and VSi2 with different vacancies are brittle, and the atomic vacancies can improve the ductility of VSi2 slightly, but can weaken the elastic modulus. The order of elastic anisotropy is Si-va3 > Si-va1 > Si-va2 > V-va2 > V-va1 > perfect VSi2 . The Si–Si and V–Si bonds are broken after Si or V atoms removed, resulting in the decreasing bond strength in VSi2 with vacancies, and eventually leading to the lower phase stability and elastic moduli of VSi2 with vacancies compared to the perfect VSi2 . The calculated sound velocities also show anisotropy.